Efek Proteksi Ekstrak Buah Naga Putih (Hylocereus undatus) terhadap Jumlah Sel Spermatid Mencit (Mus musculus) yang Dipapar Asap Rokok - Wida Pratiwi Oktavia; Muthmainah . .; Yulia . Sari (Nexus Biomedika, 2013)
Background: White dragon fruit (Hylocereus undatus) contains vitamin C, E, A and polyphenol as antioxidant. This study aimed to prove the effects of white dragon fruit to to increase number of mice spermatids that exposured by cigarette smoke and to know what the effect of the increasing dose of the extract to the number of mice spermatid. Methods: This study was an experimental laboratory research with the posttest only control group design. The subject of this research were 28 male Swiss Webster mice (Mus musculus), aged 812 weeks and 20 grams weight. The subjects were arranged by incidental sampling into 4 groups that each group consisted of 7 mice. The negative control group (KKn) was adminstered aquadest while the positive control group (KKp) was exposured by cigarette smoke. The first treatment group (KP1) and the second treatment group (KP2) was successively administered 70 mg and 140 mg white dragon fruit extract per 20 g body weight. Two hours later, the subjects in KP1 and KP2 were exposured to cigarette smoke. This treatments were conducted for 14 days. On day 15th, subjects were sacrificed with neck dislocation and both testicles were stained with HE for microscopy study. The data were analyzed with Kruskall-Wallis test and Mann-whitney test (?=0.05) Results: Mean of spermatids mice in KKn, KKp, KP1 and KP2 were 358.2916.222; 241.1436.953; 375.7974.785; and 436.1433.629, in a row. Kruskall-Wallis test showed that the significance value was 0.000 (p <0.05). Mann-Whitney test showed significant differences between KKn-KKp, KKn-KP2, KKp-KP1, KKp-KP2, KP1-KP2 and no significant difference between the KKn - KP1. Conclusion: The white dragon fruit extract inhibited the number of damage spermatids of mice that exposured by cigarette smoke and the increasing doses of the extract enlarged the number of spermatids mice exposured by cigarette smoke Keywords: white dragon fruit extract, cigarettes, mice spermatid damage